The use of blogs in EFL teaching - Güttler, Fernanda (BELT - Brazilian English Language Teaching Journal, 2011)
Abstract: This paper aims at making a review of positive experiences that used blogs in classrooms of English As a foreign language. Initially a review was done concerning the concept and history of blogs. For this review, five articles from researchers of different countries were selected in order to obtain positive reports on the use of blogs in EFL focusing on improving reading, writing and vocabulary building. Despite not being very popular in Brazil, the use of blogs as a learning tool is being largely developed and researched in other countries and it has shown good results so far. KEY WORDS: EFL; blogs; internet.